2015
DOI: 10.1177/1099636215603036
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior predictions of fiber-metal laminate/aluminum foam sandwiches under various explosive weights

Abstract: Application of blast tests causes some problems to characterize the performance of panels due to the drastic conditions of explosive medium. Real test has high safety concerns and is not easily accessible because of its extra budget. Some approaches are needed for the preliminary predictions of dynamic characteristics of panels under blast loading conditions. In this study, the response of sandwiches under blast effect was evaluated by combining quasi-static experiments and computational blast test data. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the FML based on a SRPP offers higher damping capacity than the traditional FML. Basturk et al [72] studied blast responses of sandwich panels comprising Al foam and Al/GFPP FML system were predicted by user defined the compression test results and user defined blast data. The TNT weights were chosen by considering real threats; thus, the present results have predicted the dynamic deflections under real conditions.…”
Section: Fibre Metal Laminate (Fml)mentioning
confidence: 99%
“…The results showed that the FML based on a SRPP offers higher damping capacity than the traditional FML. Basturk et al [72] studied blast responses of sandwich panels comprising Al foam and Al/GFPP FML system were predicted by user defined the compression test results and user defined blast data. The TNT weights were chosen by considering real threats; thus, the present results have predicted the dynamic deflections under real conditions.…”
Section: Fibre Metal Laminate (Fml)mentioning
confidence: 99%
“…They also have a wide range of applications in the fields of aviation [ 4 ], automobiles [ 5 ] and personal protective equipment [ 6 ]. Therefore, the honeycomb sandwich structure has always been a hot topic for scholars [ 7 , 8 , 9 , 10 , 11 , 12 ]. Rejab [ 13 ] et al focused on studying the mechanical properties of corrugated sandwich panels, which exhibit stronger impact resistance.…”
Section: Introductionmentioning
confidence: 99%